(untitled) (Research, Society and Development, 2022)
Objective: This article aims to discuss the injury prevention in childhood. Methods: Information was collected from scientific articles published in the last decade, searched in the SciELO database, in addition to updated documents and publications. Results: Safety is characterized as a child’s right. Despite this, it’s constantly violated. Injuries in the pediatric age group are configured as a public health problem because they’re the main cause of child morbidity and mortality and have repercussions in kids, their family and in the society. As injuries are a predictable and preventable condition, it’s essential to discuss the associated risk factors and exemplify preventive measures to reduce the incidence of these injuries. Conclusion: It’s perceived that the injury prevention in childhood should encompass a set of strategies, covering the three levels of coverage - primary, secondary and tertiary -, in an active and passive way, and involving early education of caregivers, supervision and legislation relevant to the social context, having more effect to ensure increasingly safer places for children.